Electron capture gas-liquid chromatographic-mass spectral identification of acids produced by Neisseria meningitidis in a defined medium. - Alley, C C (1979)
The acid metabolites and the cellular fatty acids of three strains of Neisseria meningitidis grown in a chemically defined liquid medium were determined with computerized frequency-pulsed electron capture gas-liquid chromatography. Five acids not previously reported were subsequently identified: isobutyric, octanoic, decenoic (C10:1), dodecenoic (C12:1), and tetradecenoic (C14:1). These acids were produced during active metabolism and were not detected as cellular constituents. The frequency-pulsed electron capture gas-liquid chromatography methods which we used provide a rapid, reliable, sensitive means of detecting both these and other metabolic and cellular acids in spent culture medium.